2011
DOI: 10.1063/1.3579192
|View full text |Cite
|
Sign up to set email alerts
|

Hot wire chemical vapor deposition of germanium selenide thin films for nonvolatile random access memory applications

Abstract: Thin films of germanium selenide (GexSe100−x with 0<x<57) were deposited on different substrates by hot wire metalorganic chemical vapor deposition using tetraallylgermanium and di-tert-butylselenide. The growth kinetics of the deposition process as well as the properties of the films were investigated. The growth rate was found to decrease with increasing temperature and decreasing pressure. The conformal step coverage was demonstrated. Germanium selenide films covered and subsequently diffused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…4 This phenomenon has been exploited to fabricate resistive switching devices, known as electrochemical metallization (ECM) cells, where switching between a low resistive (on) state and a high resistive (off) state is achieved through the transport of metal ions from an active electrode to an inactive electrode through a chalcogenide glass film. 5 Commonly used chalcogenide glasses for this purpose include GeSbTe, 6,7 As 2 S 3 , 8 GeSe, 7,9,10 GeTe, 11 AgGeSe, 5 and AgGeS. 12 All these devices use Ag or Cu as an active electrode.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 This phenomenon has been exploited to fabricate resistive switching devices, known as electrochemical metallization (ECM) cells, where switching between a low resistive (on) state and a high resistive (off) state is achieved through the transport of metal ions from an active electrode to an inactive electrode through a chalcogenide glass film. 5 Commonly used chalcogenide glasses for this purpose include GeSbTe, 6,7 As 2 S 3 , 8 GeSe, 7,9,10 GeTe, 11 AgGeSe, 5 and AgGeS. 12 All these devices use Ag or Cu as an active electrode.…”
mentioning
confidence: 99%
“…In addition, the IV characteristics of resistive switching devices attributed to the oxygen-vacancy mechanism display a continuous change in current during the set and reset stages, 3,23 rather than the abrupt change in current observed in our device and other chalcogenide-based devices attributed to the electrochemical-deposition mechanism. [5][6][7][8][9][10][11][12] ToF-SIMS data in Figure 4 are for devices that have been cycled through many set-reset operations, yet they show no detectable Al throughout the majority of the GaLaSO film. This indicates that, after dissolution of Al filaments following the reset operation, Al zþ ions are deposited back at the Al electrode or are swept in close proximity to the Al electrode.…”
mentioning
confidence: 99%
“…Further, none of the Ge-S films underwent extensive electrical tests according CVD reports available in literature. Referring to this, in our previous works we have demonstrated that the hot wire (HW) activation is a suitable solution for the thin film deposition of other chalcogenides (i.e., germanium antimony telluride and germanium selenide [12,13]). It is known that the HW CVD offers several advantages as the low complexity of the technique, the lack of negative plasma effects, the use of a wider range of precursors because of the catalytic character of the precursor decomposition, and the superior composition control [14].…”
Section: Introductionmentioning
confidence: 91%
“…Although 2-Mbit chalcogenide ECM memory arrays [12] and a 10 × 10 nm HfO2 based ECM cell have been demonstrated [13], the development of ECM technology is far behind that of phase change memory. The chalcogenide glasses commonly used for ECM cells are the Ge based family of glasses also commonly used in phase change memory, and include GeSbTe [14,15], As2S3 [16], GeSe [15,17,18], GeTe [19], AgGeSe [20] and AgGeS [21]. GaLaSO has a higher crystallisation temperature than most chalcogenides, which is particularly important when considering its back-end-of-line (BEOL) compatibility ie the fabrication interconnects above memory elements in a memory array [22].…”
Section: Introductionmentioning
confidence: 99%